AB0646 The Role of Serum YKL-40 in Systemic Sclerosis (SSC). (15th July 2016) - Furukawa, T.; Matsui, K.; Kitano, M.; Kitano, S.; Yokoyama, Y.; Sekiguchi, M.; Azuma, N.; Sano, H.
Abstract : Background: SSc is a refractory of connective tissue disease that causes fibrosis of the skin and various organs. 2013 ACR/EULAR classification criteria of SSc can diagnose early phase of skin involvement. Thus we considered that YKL-40 is known to be involved in inflammation, tissue fibrosis and remodeling, is an useful marker for evaluating early diagnosis and complications in SSc. YKL-40 is expressed in the synovial membrane and cartilage fibroblast cells in Rheumatoid Arthritis. However the relationship between SSc and YKL-40 is unclear. Objectives: To clarify YKL-40 is useful marker in early diagnosis in the presence or absence of complications in Japanese SSc patients. Methods: Study I: We measured serum level of YKL-40 by ELISA (Quantikine ELISA (R&D systems) ®) in 16 healthy controls and 26 SSc patients without complications: such as asthma, infection, diabetes, malignant disease, interstitial pneumonia (IP), pulmonary arterial hypertention (PAH), arthritis and other collagen disease. These complications may be increased YKL-40 levels. Study II: We measured serum level of YKL-40 by ELISA in 76 SSc patients: 42 patients without IP or PAH, 17 patients with IP, 4 patients with PAH, 13 patients with IP and PAH. We were attention to IP and PAH complications as a factor involved in the prognosis in SSc. Results: Study I: Serum YKL-40 levels were significant higher in SSc patients without complications than in healthy controls (77.3±15.8 vs 35.0±4.5ng/ml, P=0.01). On the other hand, there is no difference of YKL-40 levels due to gender, disease duration and disease type of SSc. Study II: Serum YKL-40 levels were significantly higher in SSc patients with IP and PAH than in SSc patients without IP and PAH (66.5±15.3 vs 193.4±45.3 ng/ml, P=0.01). Serum YKL-40 levels in SSc patients with IP was 92.9±28.5 ng/ml, and with PAH was 157.5±60.2 ng/ml. Conclusions: We could show increase in serum YKL-40 levels with SSc excluding complications in Japan. In contrast, Montagna reported that serum YKL-40 levels in 40 SSc patients was median 75.5ng/ml (24.2–584) including the organ complications such as heart, lung, kidney, arthritis and high CRP cases (median 0.4mg/dl, 0.3–7.5). The Complications and other factors may be influent to level of serum YKL-40. And, Nordenbaek reported SSc patients with elevated serum YKL-40 had shorter survival than patients with normal serum YKL-40 and died more often due to extensive interstisial or vascular fibrosing processes. However, there is no report on YKL-40 in SSc patients with PAH. We thought that the measure of serum YKL-40 levels in SSc patients with organ complications such as IP and/or PAH is very useful marker. We showed that YKL-40 levels are useful marker in early diagnosis of SSc with or without complications. References: Cross-sectional evaluation of YKL-40 serum concentrations in patients with systemic sclerosis. Relationship with clinical and serological aspects of disease. La Montagna G, D'Angelo S, Valentini G. J Rheumatol. 2003 Oct;30(10):2147–51. High serum levels of YKL-40 in patients with systemic sclerosis are associated with pulmonary involvement. Nordenbaek C, Johansen JS, Halberg P, Wiik A, Garbarsch C, Ullman S, Price PA, Jacobsen S. Scand J Rheumatol. 2005 Jul-Aug;34(4):293–7. Disclosure of Interest: None declared